Dê aos animais o que eles preferem: validação de um índice de preferência por meio de testes de esforço - Maia, Caroline Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Este texto é dividido em três capítulos, cada um correspondendo a um manuscrito preparado em língua inglesa e que será submetido a revistas científicas internacionais relevantes, ao menos nas áreas de comportamento e bem-estar animal. Cada capítulo (manuscrito) avalia parte das hipóteses propostas a partir da tese, como se segue: CAPÍTULO 1 – Teste das hipóteses 1 e 2. Aqui avaliamos as respostas de preferência e nãopreferência da tilápia-do-Nilo pela cor do ambiente por meio de cálculos do Índice de Preferência, com base em testes de múltipla escolha (4 opções disponíveis) realizados por 7 dias consecutivos. Tanto itens preferidos e não-preferidos bem como suas intensidades de resposta foram determinados, sendo que tais respostas foram avaliadas a nível de grupo e individualmente. Em seguida, testamos a motivação física dos mesmos indivíduos para acessar as cores ambientais anteriormente preferidas e não preferidas, registrando a frequência de tentativas dos indivíduos para acessar ambientes coloridos cujo acesso foi fisicamente, mas não visualmente, bloqueado. As respostas de motivação foram avaliadas a nível de grupo e também por indivíduo. CAPÍTULO 2 – Teste das hipóteses 3, 4 e 5. Neste estudo avaliamos as respostas de preferência do zebrafish pela cor ambiental e também por plantas artificiais em testes de escolha independentes. As preferências e não-preferências individuais e suas intensidades de resposta foram determinadas pelo Índice de Preferência, com base em testes de múltipla escolha (4 opções disponíveis) realizados por 7 dias consecutivos. Em seguida, testamos a motivação física e psicológica dos mesmos peixes, a nível individual, para acessar cores ambientais ou plantas artificiais em opções anteriormente preferidas e não preferidas. Num primeiro teste, registramos as frequências de tentativas dos indivíduos para acessar ambientes com opções previamente preferidas ou não preferidas cujo acesso foi fisicamente, mas não visualmente, bloqueado, para inferir a motivação física dos indivíduos. Num segundo teste, registramos o compartimento (com opção previamente preferida ou não preferida) que os peixes acessaram logo após cruzarem um caminho longo e aversivo, para inferir a motivação psicológica dos indivíduos. CAPÍTULO 3 – Teste das hipóteses 3, 4 e 5. Aqui avaliamos, em testes independentes, as respostas de preferência da truta arco-íris pela cor ambiental, por tocas artificiais e pela presença de coespecíficos. As preferências e não-preferências individuais, bem como suas intensidades de resposta, foram determinadas pelo Índice de Preferência com base em testes de múltipla escolha (4 opções disponíveis) realizados por 7 dias consecutivos. Em seguida, testamos a motivação física e psicológica dos mesmos peixes, a nível individual, para acessar cores ambientais, tocas artificiais ou coespecíficos em opções anteriormente preferidas comparadas àquelas não preferidas. Num primeiro teste, para avaliar a motivação física, registramos a frequência de tentativas dos indivíduos para acessar ambientes com opções anteriormente preferidas ou não preferidas cujo acesso foi fisicamente, mas não visualmente, bloqueado. Num segundo teste, para avaliar a motivação psicológica, registramos o compartimento (com opção previamente preferida ou não preferida) o qual os peixes acessaram primeiramente após cruzarem um caminho longo e aversivo.

CHAPTER 1 - Preference and motivation methods are used to identify better environmental conditions for animals, but whether there is correspondence between these methods has not previously been shown. Here we investigated this by contrasting preference and motivation for environmental colors in the fish Nile tilapia. Correspondence was demonstrated, as well as consistent individual variability for fish preferences and non-preferences, which were consistent with motivation tests. Visitation frequencies of 34 isolated fish to colored compartments (red, yellow, green and blue) were registered over 7 consecutive days. From these data we calculated values of a Preference Index, PI, as described in Maia & Volpato (A history-based method to estimate animal preference. Scientific Reports, 2016; Attachment). Then, we measured the number of pushes fish made on transparent hinged doors that blocked access to the colored compartments. Fish tended to avoid yellow color in the preference tests and were less motivated to access yellow and red colors. In contrast, they were more motivated to reach colors that they usually preferred. This shows that the preferred options indicate fish motivation. Despite this general pattern, color preference varied among fish. Thus, the PI indicates motivation for access to a resource, but in terms of which kind of resource is sought after, individuality seems to be the rule. CHAPTER 2 - Animal preferences are often inferred from choice tests, while the motivation to access preferred items is measured in terms of effort tests. What animals prefer tends to vary among individuals, but assessment of preference is often performed on groups of animals. Here, we investigated the kind of environment individual zebrafish prefer and whether they are motivated to access the preferred options. Individual fish were tested in circular aquaria evenly divided into 4 compartments. Twelve fish were allowed to choose between compartments with different background colours, while 12 other fish chose between compartments with different kinds of artificial plant. Visitation frequency in the compartments was registered every 30 s during 1 h trials that were performed over 7 consecutive days. These observations were used to calculate a preference index score for each fish. Individual fish were then tested in two kinds of motivation test. (i) A physical effort test: fish were put into a dark chamber with four transparent, hinged doors that faced the different choice compartments, and the frequency of pushes on each door was quantified to infer the motivation of the fish to access different options. (ii) A psychological effort test: fish had to swim across an open, brightly lit area to access compartments that were their primary preference; secondary preference (or the least non-preferred item); or the compartment that they had shown least interest in. The fish showed significant individual variability in their preferred options and in the strength of preference for these options. Moreover, fish were willing to push more on hinged doors that had access to their most preferred compartments compared to other available choices. When forced to cross a brightly lit open area, more fish selected to enter their primary preference compartment. We conclude that there is variation among individuals in terms of their preferences and that zebrafish are physically and psychologically motivated to gain access to their most preferred options. CHAPTER 3 - Animal preference and motivation have been used to assess different kinds of environmental resources that may help improve welfare conditions. However, preference and motivation are typically tested separately, and these assays disregard the individual nature of responses. Here, in rainbow trout, we evaluated individual variability of preference for different resources, and whether these fish are motivated to access such preferred options. Individual fish were allowed to sample among 4 different compartments. Two different kinds of test were used, one where the compartments varied in background color, the other where the compartments varied in what they contained. Over a series of 10 days, the fish interacted with these different options and during the trials of the last 7 days their visitation frequency to each compartment was registered every 30 s. The data were used to calculate a preference index for each fish. Physical motivation of individual fish to access preferred and non-preferred options was then tested by quantifying the frequency of pushes the fish gave to transparent hinged doors that led to the different compartments. In a separate test, whether fish entered a preferred or a nonpreferred option after crossing an aversive open and brightly long area was used as a measure of psychological motivation. Trout showed a strong preference for blue backgrounds, and were both more physically and psychologically motivated to access this color. However, preference and motivation for alternative items such as shelters or conspecifics were more variable. These results show that the physical and psychological motivation of trout depend on the resources that they are trying to access, but the fish express stronger motivation to gain access to more preferred options.
Give the animals what they prefer: validation of a preference index by effort tests
Keywords: Esforço físico; Esforço psicológico; Motivação; Preferência